Students’ and Lecturers’ Perspective on Code-Switching in ELT Classroom in Faculty of Education and Vocational Studies at Universitas Lancang Kuning - Lee, Kenan; Syaifullah; Herdi; Abbas, M. Fadhly Farhy (Jurnal Indragiri Penelitian Multidisiplin, 2024)
This study explores the perspectives of students and lecturers on code-switching within the English Language Teaching (ELT) classroom context at Lancang Kuning University. Employing a qualitative approach, this research utilized descriptive qualitative methods to delve into the perspective of the participants. Semi-structured interviews, guided by adapted questionnaires, were conducted with three examiner lecturers and four 7th-semester students from the English Education Department. Video recordings supplemented the data collection process. Lecturers strategically employed code-switching to enhance clarity and comprehension, particularly during seminar proposals and result presentations. Students acknowledged its usefulness in aiding understanding, especially in the face of low English proficiency levels. However, concerns were raised regarding potential overuse hindering English language development. Code-switching notably improved students' speaking performance and engagement in ELT classrooms. The study underscores the multifaceted role of code-switching in ELT classrooms, balancing its benefits for comprehension and engagement with concerns about its impact on English proficiency